A mid-Oligocene (Whitneyan) rhinocerotid from northeastern California. (9th March 2015) - Bright, Jen A.; Tiffney, Bruce H.; Wyss, André R.
Abstract: Rhinoceroses were important in North American mammal faunas from the late middle Eocene to the Miocene, but the group's poor sampling outside the High Plains and eastern Rocky Mountain regions during their early evolution significantly hinders understanding of their biogeography. This limited geographic sampling is particularly true of early–middle Oligocene time, with the vast majority of Whitneyan localities occurring in the White River Badlands of South Dakota. Thus, any rhinocerotid from outside the High Plains during this period is significant. We describe two new rhinocerotid specimens from the middle Oligocene Steamboat Formation of the northeastern Warner Mountains of California. Although the Steamboat Formation is well known for fossil plants, this is the first report of mammalian fossils from the area: an isolated lower molar recovered in 1974 but not previously described or illustrated, and a mandibular fragment recovered approximately 20 years later and bearing two molar teeth, most likely pertaining to the same taxon and horizon. The lack of distinctive morphological characters suggests both fossils be conservatively referred to Rhinocerotidae incertae sedis. Based on published tooth measurement data, Trigonias osborni represents the closest size match, but that species is currently only known from the Chadronian. Similarly, the Whitneyan taxon Diceratherium tridactylum is approximately the right size, but is currently only known from the High Plains and its presence in California would expand its geographic range substantially. Of greatest importance here is that sediments of the eastern Warner Mountains may represent a largely unexplored locale for early–middle Oligocene fossil vertebrates, and may yield important future finds.